Public institutions and gender relations in sustainable forest management, Cintalapa, Chiapas - Palacios Vázquez, Ana Lilia; Pérez Nasser, Elia; Pérez Olvera, Ma. Antonia (Revista Mexicana de Ciencias Agrícolas, 2017)
This research analyzes gender relations in two rural  communities in Cintalapa municipality, Chiapas, within the  La Sepultura Biosphere Reserve and the influence of public  institutions related to sustainable forest management. Forest  management is based on techno-scientific aspects that  prioritize valuable resources in the market at the expense  of biodiversity and resources relevant to women; it is a  reductionist management strategy that partially perceives  the forest. The public environmental management system, on  the one hand, empowers public environmental institutions to  manage and regulate forest resources considered technically  fit for use; on the other hand, it promotes the conservation  of biodiversity through natural protected areas, and should  therefore address gender mainstreaming in all programs.  Data collection in the field research conducted in 2014 was  done through: eight semi-structured interviews with key  actors, two group interviews differentiated by sex, four  differentiated participatory workshops, and a survey of 33  women and 28 men. It was found that public institutions  accentuate gender gaps through public programs aimed  at women with no gender perspective, due to the lack of  knowledge of the subject; so that, traditional division of  labor is reinforced based solely on difference by sex.
Keywords: conservation and management, gender gaps, sustainable forest development